Three-dimensional analysis of yurchenko layout with 360° twist in female vaults: modified deterministic model and judges' scores - Kim, Y.-K.; Park, C.-H. (ISBS Proceedings Archive (Michigan), 2017)
The purposes of this study were to identify kinematic variables that govern successful performance and judges' scores and to establish correlative relationships among those variables of Yurchenko layout with a full twist in female vaults. Thirty-two vaults data were collected from national competition by four video cameras (60Hz sampling rate). The obtained scores from judges` decision were mainly affected by post-flight peak height, horse contact time, knee angle at landing, and horse take-off angle. Modified deterministic model showed that round-off entrance and take-off angles and resultant velocity of the CM were the starting variables affecting performance in following kinematic variables. Knee angle at landing, a highly influential variable on the obtained point, was only determined by judges` decision without significant relationship with previous kinematic variables.